MENGEMBANGKAN KEMAMPUAN MOTORIK KASAR MELALUI PERMAINAN LOMPAT TALI PADA KELOMPOK B1 DI TK RAUDHATUL JANNAH TAHUN AJARAN 2017/2018 - Nurul Hidayati Ramdany; I Nyoman Suarta; Nurhasanah Nurhasanah; N. L. P Nina Sriwarthini (Jurusan Ilmu Pendidikan FKIP Universitas Mataram, 2021)
Physical development is closely related to gross motor development. To develop gross motor skills, it can be developed through the Jump Rope Game. This research was motivated by the results of observations at Raudhatul Jannah Kindergarten related to the gross motoric development of children who are still not optimally developed. Based on the facts in Raudhatul Jannah Kindergarten, it shows that 7 out of 10 children still have not developed their gross motor skills, while the remaining 3 children show that their gross motor skills are quite developed, so the problem formulation of this study is how to develop gross motor skills through jumping rope games in group B1 in Raudhatul Jannah Kindergarten in the 2017/2018 Academic Year. The purpose of this study was to find out that the jump rope game can develop the gross motor skills of children in group B1 at Raudhatul Jannah Kindergarten in the 2017/2018 academic year. This type of research is development research. The subjects in this study were 10 children consisting of 6 girls and 4 boys. The method used to collect data is the method of observation and documentation method as well as data analysis using quantitative descriptive techniques. The results showed that in the development stage I reached an average value of 54.83% while in the development stage II it began to increase with an average value of 66.7% and increased optimally in the third development stage with a percentage of 85.21%. . Based on the results of this study, it can be concluded that the jump rope game performed with the right steps can develop gross motor skills in children in group B1 at Raudhatul Jannah Kindergarten Mataram.